2008
DOI: 10.1007/s11751-008-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of displaced supracondylar humeral fractures in children by percutaneous lateral cross-wiring technique

Abstract: Seventy children with displaced type II and III supracondylar fractures of the humerus were managed with percutaneous lateral cross-wiring technique from January 2006 to January 2007. There were 54 boys and 16 girls with a mean age of 6.1 +/- 3.07 years. All patients were operated within 24 h after trauma using the Dorgans percutaneous lateral cross-wiring technique. Patients were followed up for a mean period of 6.1 +/- 2.6 months and assessed both radiologically for union; and functionally and cosmetically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In our study a rate of 9% ulnar nerve damage was seen in medial and lateral cross-wire cases. However, there have been no reports of iatrogenic ulnar nerve damage from lateral cross-wire configuration [3,13]. As our cases which were treated with lateral cross-wire configuration showed no iatrogenic ulnar nerve damage, it is thought that in the treatment of paediatric supracondylar fractures, the use of lateral cross K-wires may reduce the possibility of iatrogenic ulnar nerve damage.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our study a rate of 9% ulnar nerve damage was seen in medial and lateral cross-wire cases. However, there have been no reports of iatrogenic ulnar nerve damage from lateral cross-wire configuration [3,13]. As our cases which were treated with lateral cross-wire configuration showed no iatrogenic ulnar nerve damage, it is thought that in the treatment of paediatric supracondylar fractures, the use of lateral cross K-wires may reduce the possibility of iatrogenic ulnar nerve damage.…”
Section: Discussionmentioning
confidence: 55%
“…In recent biomechanical studies it has been shown that cross-wire pinning configuration is the most stable fixation technique [7]. Although loss of reduction is high in lateral divergent pinning at 28%, only 2% have been reported for cross-wire fixation, and no loss of reduction cases have been reported for all lateral crosswire pinning in the literature [3,13]. In our study loss of reduction was detected as 2.6% for cross-wire and 1.5% for all lateral cross-wire fixation groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is comparable with other studies. 87.5% achieved satisfactory outcome after fixation using 2 lateral wires inserted through the trochlea-capitellar junction 10 ; 80% achieved satisfactory outcome after fixation using crossed medial-lateral and lateral wires 11 ; 91.4% achieved satisfactory outcome after fixation using lateral cross wires 12 ; 91.9% to 96.3% achieved excellent/good outcome after fixation using one to 2 posterior intrafocal wires 8 ; 95% to 100% achieved excellent/good outcome after a pin leverage technique for reduction and 2 to 3 lateral wires for fixation. 9 Although the transolecranon wire limits the flexion and extension of the elbow, this did not affect the final outcome as the elbow was fixed in a plasterof-Paris splint for a minimum of 3 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…We use Dorgan's technique for fixation of medial oblique fractures for which the lateral divergent Kirschner (K)-wire configuration is suboptimal [5]. Although some authors claim minimal risk for radial nerve injury by this technique, the ideal limits for safe placement of the proximal entry pin in coronal and transverse planes have not been defined on the basis of evidence [8][9][10]. This pin may, however, risk damage to the radial nerve because of its close proximity to the anterior and lateral surfaces of the distal humerus.…”
Section: Introductionmentioning
confidence: 99%